Does Participating in Sports Activities Alleviate The Impact of Perceived Social Support on Cross-Cultural Adaptation? - Wang, Yuqing (Transactions on Social Science, Education and Humanities Research, 2026)
With the deepening of the Internationalising academic programmes, The issue of how to better support international students through cultural adaptation is gradually becoming the focus of educational discussions. This study investigated the relationship between Perceived Social Support (PSS), Sports Participation (SP), Cultural Distance (CD) and Cross-Cultural Adaptation (CCA) among 503 international students from Japanese universities. Using the cross-sectional survey method, a verified scale is used to evaluate the subjects’ views on social support, social and cultural adaptation, sports participation and perceived cultural distance. Through structural equation model and hierarchical regression analysis, the direct effect, intermediary effect and regulatory effect are discussed. Perceived social support has become an important factor in promoting cross-cultural adaptation. Sports participation not only helps to adapt independently, but also acts as a part of the way for social support to play a role. In addition, cultural distance has a negative regulatory effect on the relationship between sports participation and adaptation, that is, as the perceived cultural distance increases, the positive effect of sports participation gradually weakens, although its impact is still significant. These findings show that sports participation is an important behavioural path for social support to promote social and cultural adaptation of international students, and cultural distance acts as a contextual constring factor.